Crisis communication based on the example of cases in the Croatian Mountain Rescue Service - Mihalinčić, Martina; Granić, Josip; Turčić, Ivica (Crisis Management Days, 2024)
Given the current global situation encompassing climate change, natural disasters, war threats, terrorism, and many other hazards, it is almost certain to conclude that we are living in times of crisis. Therefore, it is crucial that we actively address these challenges and do not allow them to dominate us. Crisis management discipline becomes increasingly important in such circumstances. This discipline enables organizations and individuals to effectively manage crisis situations by recognizing risks, planning responses, and acting quickly to mitigate consequences. Additionally, crisis management seeks to prevent or minimize negative crisis outcomes and thereby protect the organization, stakeholders, and/or industry from harm (Coombs, 1999). A crucial component of this is crisis communication. The importance of crisis communication is best seen in the saying that a crisis is not what happened but how the public perceives what happened. In a narrow sense, crisis communication involves the exchange of information, opinions, attitudes, and even emotions before, during, and after a crisis. In a broader sense, it is defined as the collection, processing, and dissemination of necessary information to deal with a crisis. Without effective crisis communication, crisis management can be significantly hindered, as communication plays a crucial role in managing the perception of external stakeholders, media, employees, and the public during crisis situations. Therefore, crisis communication is integrated into all phases of crisis management to ensure effective crisis management. In order for crisis communication to be adequate, certain principles have been recognized, according to Coombs (2007): 1) Take control and communicate clearly; 2) Present information unambiguously, clearly, and vividly; 3) Approach the media calmly and confidently; 4) Inform all potential spokespersons with the most up-to-date information about the crisis and the key messages the organization is trying to convey; 5) Inform the internal audience/employees about the crisis and crisis action; 6) Sincerely show concern for the newly arising problem and its consequences, as well as for the people affected by it. This paper analyzes two cases of crisis communication using the example of the Croatian Mountain Rescue Service according to the mentioned principles. The purpose of the analysis using the case study method is to highlight good and bad examples and to provide conclusions and recommendations for future crisis communication, both for the Croatian Mountain Rescue Service and related organizations